The Role of Accounting Learning in Forming Anticorruption Character at SMK Negeri 1 Banjarmasin - Kamaliah, Nurul; Rizky, Maulana; Nor, Baseran; Ratumbuysang, Monry Fraick Nicky Gillian (Jurnal Pendidikan Ilmu Sosial, 2023)
This research aims to determine the role of accounting learning in forming anti-corruption character at SMK Negeri 1 Banjarmasin. The research method used in this research is an experimental method using a quantitative research approach. The research subjects were 135 class XII students of the institutional financial accounting skills program. The sampling technique used in this research was purposive random sampling. While the data collection technique is through questionnaires and documentation, the data analysis used in this research is a structural model or inner model by calculating R-Square or coefficient of determination (R2), path coefficient estimation, and Hypothesis Testing (re-sampling and bootstrapping). The results of data analysis show that there is a positive and significant relationship between the role of accounting learning and the formation of anti-corruption character. This research is the initial stage in triggering students' anti-corruption character.